Study of well water quality and heavy metal content in urban and rural area: case study at Kota Bharu and Pasir Puteh, Kelantan - Talib, Norishah Abd (Universiti Sains Malaysia, 2015)
Groundwater quality whether at urban or rural area can be influenced by natural factors and anthropogenic activities. Urbanisation, agriculture and industrial are examples of anthropogenic activities while interactions of rocks, soils, natural disasters are natural factors that can influence quality of groundwater. In this study, a total number of 60 water samples were collected from wells at urban and rural area. Water sample were analysed for water quality and heavy metal parameters. The results were compared to standard drinking water by Ministry of Health (MOH) and Interim National Water Quality Standard (INWQS) for classification of Water Quality Index (WQI) value. Result indicates that well water quality of sampling locations was classified to class III. The value for each parameter are in the range of 4.44 - 7.7 mg / L, 1.0-3.8 mg / L, 4.7- 60 mg / L, 0.01- 1.0 mg / L, 0.7- 13.7 mg / L, 4.3-8.0 for DO, BOD, COD, NH3N, SS and pH respectively and undetected to 3.9 mg / L, undetected to 0.005mg / L, 0002- 0009 mg / L, 0001 -0009 mg / L for Fe, Cd, Mn and Pb content respectively. Comparison of water quality and heavy metals parameters between Kota Bharu and Pasir Puteh was carried out using an independent t-test. The results showed significant differences between the two areas, with p <0.05 except for both Fe and Mn which showed p >0.05.